The 'university place' : how and why place influences the engagement and retention of Aboriginal and Torres Strait Islander university students : final report. - Raciti, Maria M.; Carter, Jennifer; Gilbey, Kathryn; Hollinsworth, David (Australia. Dept of Education and Training (DET), 2018)
This seed project aimed to enhance Aboriginal and Torres Strait Islander university student engagement and retention. Specifically, this project attended to the notion of the 'university place' and provides information and two tools that universities can use to help optimise the persistence and educational outcomes of Indigenous Australians. This project has produced meaningful, useful and novel contributions that are relevant to the sector. Central to this seed project is the notion of place. Place is broadly defined as 'space + meaning' (Harrison & Dourish 1996). People's identity is intertwined with places and, as such, people and places are knitted together (Sack 1997). Even so, the relationship between people's identity and place is often overlooked (Malpas 1999). Place is defined as the experiential setting that consists of a specific location and the cognitive, emotional, behavioural and social activities that occur within (Relph 1976). People alter their identity to help them navigate places (Baumeiser & Muraven 1996). Thus, the 'university place' comprises cognitive, emotional, behavioural and social activities in a locale that transpires across students' university experience and with which their identity is intertwined. For this project, a case study approach comprised of two universities and employed mixed methods that were organised into three stages. Stage 1 included the collation of baseline data from the participating universities (e.g. Indigenous student enrolment numbers) and beginning-project presentations. Stage 2 comprised interviews and focus groups from which qualitative data was collected from: a) undergraduate and postgraduate Indigenous university students; b) academic teaching staff; and c) relevant administrative, professional and technical (APT) staff. From this qualitative data, a framework was developed and was discussed at mid-project presentations and disseminated in the mid-project report. Finally, in Stage 3 quantitative data was collected via surveys of: a) undergraduate and postgraduate Indigenous students; and b) academic teaching staff. Stage 3 served to evolve the framework and develop the two project tools. End-project presentations, workshops, publications and an e-booklet served to widely disseminate the findings. [Executive summary, ed]